Validitas Video Pembelajaran Matematika Berbasis Power Point Untuk Peserta Didik Kelas VIII SMPN 2 Sintuk Toboh Gadang - Yuliani Fitri; Ayesha Aftiadi (Departement of Mathematics Education, 2022)
This study is based on the lack of students’s interest on mathematics subject, the teacher only used text book where its display is not interesting at all for the students. Beside that, the lack of the students’ interest is also due to unavailable IT based - teaching media at school. The purpose of the study is to figure out the validity of teaching video of mathematics subject based on power point, which is developed for the students of grade VIII of SMPN 2 Sintuk Toboh Gadang. Developing model used is ADDIE, analysis, design, development, implementation, and evaluation. Products were validated by three validators, 2 mathematics lecturers, 1 Indonesian lecturer. The result of validation shows that 87,29% mean of design which is very valid, 75% of pedagogical aspect which is valid, 82,29% of content validity which very valid, and 83,38% of language validity which is very valid. Therefore, generally, the video designed is valid and can be tested.